Sylvia Rafael : The Life and Death of a Mossad Spy - Oren, Ram (Book collections on Project MUSE., 2014)
""There is a lack of quiet in Sylvia that craves for action ... She knows that she is special and that she possesses unusual and varied abilities.""--The Mossad''s psychological evaluation of Sylvia RafaelWhen Moti Kfir, head of the Academy for Special Operations of the Mossad, first interviewed Sylvia Rafael in a coffee shop, he knew she would make a great combatant for Israel''s intelligence agency. She was outgoing, resourceful, brilliant, and had a talent for bonding with others. When Kfir warned her that the mysterious job they''d met to discuss could be dangerous, she simply sat b.